1990
DOI: 10.1172/jci114747
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for altered epicardial coronary artery autoregulation as a cause of distal coronary vasoconstriction after successful percutaneous transluminal coronary angioplasty.

Abstract: To determine whether vasoconstriction distal to the site of successful percutaneous transluminal coronary angioplasty (PTCA) is a result of altered autoregulation in a hypoperfused coronary artery, we examined the association of this distal vasoconstriction with lesion severity in 20 patients. Lesion severity was classified as moderate, severe or critical (> 1.0, 0.5-1.0, and < 0.5 mm, respectively). Quantitative coronary measurements were made at 3, 15, and 30 min after PTCA, and then after intracoronary (IC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Vasoconstrictive responses after balloon angioplasty have been reported [33] and attributed either to altered coronary artery autoregulation [34], or local effects of platelet-derived vasoactive substances such as serotonin [35]. However, these changes in vascular tone distal to the site of angioplasty disappear usually within the first days after intervention and are unlikely to persist up to 6 months after intervention.…”
Section: Vascular Dysfunction After Drug-eluting Stent Implantationmentioning
confidence: 99%
“…Vasoconstrictive responses after balloon angioplasty have been reported [33] and attributed either to altered coronary artery autoregulation [34], or local effects of platelet-derived vasoactive substances such as serotonin [35]. However, these changes in vascular tone distal to the site of angioplasty disappear usually within the first days after intervention and are unlikely to persist up to 6 months after intervention.…”
Section: Vascular Dysfunction After Drug-eluting Stent Implantationmentioning
confidence: 99%
“…A series of recent studies has related epicardial coronary vasoconstriction that has been reported early after PTCA 46,47 to ␣-adrenergic activation. 48 -52 Gregorini et al 48 observed a constrictor response not only of the culprit segment and a distal segment of the vessel that underwent PTCA but also of the nonmanipulated control vessel.…”
Section: ␣-Adrenergic Coronary Vasoconstriction During Interventionsmentioning
confidence: 99%
“…These findings are in accordance with other studies that demonstrated an impaired coronary flow reserve immediately after balloon angioplasty, compared with normal values of the control group, due to an increased baseline coronary blood flow. 10,16 Several mechanisms have been postulated for the observed increase in baseline flow velocity after PTCA, such as (1) failure of the peripheral arterial vascular bed to vasoconstrict appropriately on the sudden increase in distal coronary pressure produced by coronary angioplasty, (2) epicardial vasoconstriction at the site of the Doppler guidewire tip mediated by a myogenic response and/or neural mechanisms, 17,18 or (3) the influence of drug therapy. 19,20 However, all patients were treated with nitroglycerin during the procedure, and there was no difference in drug therapy (nitrates, calcium antagonists, ␤-blockers, or ACE inhibitors) between patients with and without impaired CFR after PTCA.…”
Section: 6mentioning
confidence: 99%